Timing of allergenic food tntroduction to the infant diet and risk of allergic or autoimmune disease: a systematic review and meta-analysis - Ierodiakonou, Despo; Garcia-Larsen, Vanessa; Logan, Andrew; Groome, Annabel; Cunha, Sergio; Chivinge, Jennifer; Robinson, Zoe; Geoghegan, Natalie; Jarrold, Katherine; Reeves, Tim; Tagiyeva-Milne, Nara; Nurmatov, Ulugbek; et al. (American Medical Association, 2016)
Importance: Timing of introduction of allergenic foods to the infant diet may influence the risk of allergic or autoimmune disease, but the evidence for this has not been comprehensively synthesized. Objective: To systematically review and meta-analyze evidence that timing of allergenic food introduction during infancy influences risk of allergic or autoimmune disease. Data Sources: MEDLINE, EMBASE, Web of Science, CENTRAL, and LILACS databases were searched between January 1946 and March 2016. Study Selection: Intervention trials and observational studies that evaluated timing of allergenic food introduction during the first year of life and reported allergic or autoimmune disease or allergic sensitization were included. Data Extraction and Synthesis: Data were extracted in duplicate and synthesized for meta-analysis using generic inverse variance or Mantel-Haenszel methods with a random-effects model. GRADE was used to assess the certainty of evidence.